Poly(2-methyl-2-oxazoline) and poly(4-vinyl pyridine) based mixed brushes with switchable ability toward protein adsorption. (November 2019) - Atif, Muhammad; Chen, Chaoshi; Irfan, Muhammad; Mumtaz, Fatima; He, Kang; Zhang, Miao; Chen, Lijuan; Wang, Yanmei
Graphical abstract: Highlights: PMOXA/P4VP based coatings were prepared by a simple annealing protocol. PMOXA/P4VP based surfaces possess pH stimuli-responsive properties. Switchable BSA adsorption/desorption were achieved by PMOXA/P4VP based coatings. Abstract: In this work, poly[(2-methyl-2-oxazoline)-random-glycidyl methacrylate] (PMOXA-r-GMA) and poly(4-vinyl pyridine)-block-poly(glycidyl methacrylate) (P4VP-b-PGMA) were synthesized by cationic ring opening polymerization (CROP) of 2-methyl-2-oxazoline (MOXA) and reversible addition-fragmentation chain transfer (RAFT) polymerization of 4-vinyl pyridine (4VP) followed by their random and block copolymerization with glycidyl methacrylate (GMA), respectively. Then poly(2-methyl-2-oxazoline)/poly(4-vinyl pyridine) (PMOXA/P4VP) based binary polymer brushes on silicon/glass substrate were fabricated using spin coating of the mixture of PMOXA-r-GMA and P4VP-b-PGMA copolymer solution followed by annealing process at 110 °C. Afterwards, these polymer brushes were characterized via water contact angle (WCA), X-ray photoelectron spectroscopy (XPS), variable angle spectroscopic ellipsometry (VASE), and atomic force microscopy (AFM) techniques. The results showed that the surface composition on the substrate surface could be adjusted by tuning the composition of the mixture of polymer solution used for the preparation of mixed brushes. Moreover, it also showed the swelling and de-swelling of mixed polymer brushes in a systematic way between two specific points during varying the pH of the surrounding medium from 2 to 10. Finally, the tunable behavior of PMOXA/P4VP based mixed brushes against bovine serum albumin (BSA) adsorption/desorption was investigated by fluorescein isothiocyanate-labelled BSA (FITC-BSA) assay and ellipsometry measurements. The results indicated that by changing the pH value from 2 to 10, the PMOXA/P4VP based mixed brushes could adsorb and desorb protein from very low to high amount depending upon the composition of PMOXA-r-GMA and P4VP-b-PGMA in preparing solution used for the PMOXA/P4VP based coatings, and ~89% of the adsorbed protein could be desorbed under the selected conditions.